2019
DOI: 10.2147/ppa.s192735
|View full text |Cite
|
Sign up to set email alerts
|

<p>Adherence to HIV treatment regimens: systematic literature review and meta-analysis</p>

Abstract: Background Antiretroviral therapy (ART), when taken consistently, reduces morbidity and mortality associated with human immunodeficiency virus and viral transmission. Suboptimal treatment adherence is associated with regimen complexity and high tablet burden. Single-tablet regimens (STRs) provide a complete treatment regimen in a single tablet. This study examined the relationship between STRs (vs multiple-tablet regimens [MTRs]), treatment adherence, and viral suppression. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
125
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(141 citation statements)
references
References 58 publications
3
125
0
3
Order By: Relevance
“…Outcome measures, including adherence and persistence during the follow-up period were measured. In HIV, a high level of adherence to ART is required for viral suppression [13]. However, thresholds for categorizing "adherent" versus "non-adherent" differ across studies (e.g.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Outcome measures, including adherence and persistence during the follow-up period were measured. In HIV, a high level of adherence to ART is required for viral suppression [13]. However, thresholds for categorizing "adherent" versus "non-adherent" differ across studies (e.g.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…STRs are single-dose units administered once-daily, whereas multi-tablet regimens (MTRs) require multiple dosing units per day [4]. STRs may improve adherence, thus resulting in greater efficacy, reduced risk of virologic failure, and prevention of the emergence of drug resistance [13,14]. The decision to prescribe STRs vs MTRs is based to a large extent on patient and clinician preference as well as, in some instances, medication cost and positioning of products on payer formularies [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite the increased availability of antiretroviral medications, HIV-related morbidity, mortality, and new infection rate continually increased over the years in China from 2004 to 2016 [1]. Both clinical trials and cohort studies have shown that the effectiveness of antiretroviral medications is highly dependent on adherence [2][3][4]. Suboptimal adherence severely undercuts antiretroviral effectiveness and places PLHIV at risk for virologic failure, increases the risk of onward HIV transmission, and limits the impact of HIV treatment resources [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…PLHIV on ART who are not retained in care are at increased risk of developing drug resistance and dying [4]. Based on a systematic review of several studies that have been conducted in low resource settings, key predictors of high attrition include patients with advanced HIV-disease progression [marked by body mass index (BMI) <18 kg/m 2 , baseline CD4 counts <200 cells/mL, World Health Organisation (WHO) Stage - III and IV, poorer level of functionality], male sex, younger age and having lower levels of education [5].…”
Section: Introductionmentioning
confidence: 99%